Insulated screwdriver and preparation method thereof

By stacking the Zr-Al-N composite permeability layer, AlN-ZrO2 intermediate plating layer and surface insulating layer on the screwdriver's driver's driver's driver's conductivity in a high voltage environment, the effect of maintaining insulation at high voltage and improving wear resistance is achieved.

CN117484431BActive Publication Date: 2025-03-28SHENZHEN HUAYUFA VACUUM ION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311376039.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-03-28
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

The driver rods of existing screwdrivers conduct electricity in high voltage environments, resulting in arc sparks and short circuit risks, and are difficult to meet the insulation and wear resistance requirements at high voltages.

Method used

The insulating screwdriver design is adopted, including the driver rod body, the Zr-Al-N composite seepage layer, the AlN-ZrO2 intermediate plating layer and the surface insulating layer. Through processes such as quenching, tempering, co-permeation treatment, coating treatment and evaporation treatment, a high-hardness and wear-resistant insulating layer are formed.

Benefits of technology

Maintain insulation within the voltage range of 300V-1500V, improve the wear resistance and bonding of the driver rod, extend service life, and reduce the risk of arc sparks and short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117484431B_ABST
    Figure CN117484431B_ABST
Patent Text Reader

Abstract

The present application provides an insulating screwdriver and a preparation method thereof, and relates to the technical field of electrical tools. The insulating screwdriver comprises a screwdriver rod and an insulating handle, and the screwdriver rod comprises a screwdriver rod body and a Zr‑Al‑N composite infiltration layer, an AlN‑ZrO2 intermediate coating layer and a surface insulating layer sequentially stacked on the surface of the screwdriver rod body. The preparation method of the insulating screwdriver comprises: after quenching and tempering the screwdriver rod body, Zr‑Al‑N co-infiltration treatment, AlN‑ZrO2 vacuum coating treatment, and evaporation treatment are sequentially performed to obtain the insulating screwdriver. The insulating screwdriver prepared by the present application can maintain insulation at a voltage of 300V‑1500V, and the coating on the surface of the screwdriver rod body has a high bonding force, is difficult to fall off, has high hardness, and has good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrical tools, and in particular to an insulating screwdriver and a preparation method thereof. Background Art

[0002] Screwdrivers are commonly used tools for electricians, and are used to install, tighten or loosen screws when connecting wires of various electrical components. The screwdriver shaft of a screwdriver needs to be in direct contact with the screw and also needs to withstand torque when installing the screw. Therefore, it is generally made of metal steel, but metal materials are conductive. However, in the field of electricity, the installation volume of various electrical components is large, and workers often need to install them under power. If the screwdriver shaft of a screwdriver is conductive during installation, especially when the voltage is high, the insulation performance is poor, which will cause the following consequences: (1) When the screwdriver shaft is buckled into the screw slot and when it is withdrawn from the screw slot, it is easy to generate arc sparks, which brings danger to the operator; (2) The distance between the terminals in some electrical components is too close, and the screwdriver shaft is easy to touch the nearby terminals or wires when tightening the screws, causing a short circuit. Therefore, for screwdrivers that are installed under power, the screwdriver shaft must be insulated.

[0003] In addition, when performing high-voltage power operations, it is also necessary to use a high-voltage resistant insulated screwdriver to ensure the safety of the operation. The requirements for this screwdriver are: (1) the screwdriver remains insulated within the voltage range of 300V-1500V; (2) the screwdriver has good wear resistance, and the screwdriver rod can still remain insulated after tightening and loosening 10,000 times at the set torque. However, it is difficult for existing products to meet the requirements for use under high voltage. There is an urgent need to design a high-voltage resistant insulated screwdriver to ensure the safety of high-voltage operations. Summary of the invention

[0004] In order to solve the above-mentioned defects, the present application provides an insulating screwdriver and a preparation method thereof, which can be used in scenarios where power operations are performed under high voltage.

[0005] To achieve the above objectives, the technical solution of this application is as follows:

[0006] The present application provides an insulating screwdriver, comprising a screwdriver rod and an insulating handle, wherein the screwdriver rod comprises a screwdriver rod body and a Zr-Al-N composite diffusion layer, an AlN-ZrO2 intermediate coating and a surface insulating layer sequentially stacked on the surface of the screwdriver rod body.

[0007] Preferably, the surface insulating layer includes at least one of a nylon 66 film layer, a polytetrafluoroethylene film layer and a rubber layer.

[0008] Preferably, the thickness of the Zr-Al-N composite diffusion layer is 10 μm-20 μm;

[0009] The thickness of the AlN-ZrO2 intermediate coating is 3 μm-6 μm;

[0010] The thickness of the surface insulating layer is 4 μm-6 μm.

[0011] Preferably, the material of the screwdriver rod body includes any one of chrome steel, chrome vanadium steel, chrome-molybdenum steel, and chrome-molybdenum-vanadium steel.

[0012] The present application also provides a method for preparing the above-mentioned insulated screwdriver, comprising:

[0013] After the screwdriver rod body is subjected to quenching and tempering treatments, Zr-Al-N co-penetration treatment, AlN-ZrO2 coating treatment, and vapor deposition treatment are sequentially performed to obtain the insulating screwdriver.

[0014] Preferably, the preparation method satisfies at least one of the following conditions:

[0015] a. The quenching method includes: using nitrogen, helium or argon gas quenching treatment;

[0016] b. The Zr-Al-N co-penetration treatment comprises: using a Zr-Al composite material as a target material for coating, using a dual cathode DC dual power supply, passing a nitrogen-containing mixed gas, and performing a co-penetration treatment to form the Zr-Al-N composite permeation layer;

[0017] c. The AlN-ZrO2 coating process comprises: using AlN+ZrO2 as a target material, using a medium frequency constant voltage coating power supply, performing a coating process to form the AlN-ZrO2 intermediate coating layer;

[0018] d. The evaporation treatment includes: using nylon 66 as the evaporation material, and evaporating to form the surface insulation layer under vacuum conditions.

[0019] Further preferably, the preparation method further satisfies at least one of the following conditions:

[0020] e. In the Zr-Al composite material, the mass proportion of Zr is 5%-10%, and the mass proportion of Al is 95%-90%;

[0021] f. The electrode connection method and power supply parameters of the dual cathode DC dual power supply are as follows: the cathode of one cathode power supply is connected to the Zr-Al composite material as a source, and the operating voltage is 700V-800V; the cathode of the other cathode power supply is connected to the screwdriver rod body workpiece as a cathode, and the operating voltage is 450V-550V; the anode is connected to the vacuum furnace wall and grounded;

[0022] g. The mixed gas further comprises hydrogen, and the volume ratio of the nitrogen to the hydrogen is 1:(2-3);

[0023] h. During the co-penetration treatment, the vacuum degree of the vacuum furnace is 1Pa-10Pa, and the temperature is 520℃-550℃;

[0024] i. The co-osmosis treatment time is 3h-4h.

[0025] More preferably, the volume ratio of the nitrogen to the hydrogen is 1:3.

[0026] Further preferably, the preparation method further satisfies at least one of the following conditions:

[0027] j. In the AlN+ZrO2 target, the mass proportion of ZrO2 is 5%-10%, and the mass proportion of AlN is 95%-90%;

[0028] k. The electrode connection method of the medium frequency constant voltage coating power supply is: the positive electrode of the power supply receives the workpiece to be coated, and the negative electrode is connected to the target;

[0029] l. The voltage of the medium frequency constant voltage coating power supply is 350V-400V, and the frequency is 6KHz-14KHz;

[0030] m. The coating process is carried out under vacuum conditions of 1Pa-10Pa;

[0031] n. The coating treatment temperature is 200°C-300°C and the time is 1h-2h.

[0032] Preferably, the preparation method satisfies at least one of the following conditions:

[0033] o. After the tempering treatment, the hardness of the screwdriver rod body is 700Hv-750Hv;

[0034] p. After the Zr-Al-N co-diffusion treatment, the hardness of the Zr-Al-N composite diffusion layer is 1200Hv-1250Hv.

[0035] Preferably, the vacuum condition of the evaporation treatment is 0.5Pa-0.7Pa, the temperature is 200°C-300°C, and the time is 1h-2h.

[0036] Beneficial effects of this application:

[0037] The insulated screwdriver of the present application can maintain insulation at a voltage of 300V-1500V. At the same time, the composite insulating layer on the surface of the screwdriver rod has high hardness, good wear resistance, high bonding strength with the screwdriver rod body, and is difficult to fall off. Among them, the Zr-Al-N composite infiltration layer can reduce the conductivity of the screwdriver rod body on the one hand, and increase the hardness of the screwdriver rod body on the other hand; the AlN-ZrO2 intermediate coating contains Al and Zr elements, which have an affinity effect, can improve the bonding strength between the intermediate coating and the composite infiltration layer, and further reduce the conductivity; the surface insulating layer further improves the insulation level and prevents the intermediate coating from wearing or falling off.

[0038] The preparation method of the insulated screwdriver of the present application is mature and can be mass-produced. In particular, the present application first performs a quenching and tempering process on the screwdriver rod before the coating process, which can improve the mechanical properties such as strength and hardness of the screwdriver rod body, ensure that the subsequent processes will not cause the hardness of the screwdriver rod body to decrease, and greatly improve the wear resistance of the insulated screwdriver. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0040] Figure 1 This is a schematic diagram of the structure of a screwdriver in Example 1 of the present application;

[0041] Figure 2 This is a schematic diagram of the structure of the screwdriver rod in Example 1 of the present application.

[0042] Description of Figure Numbers:

[0043] 1-insulated handle; 2-screwdriver rod; 201-screwdriver rod body; 202-Zr-Al-N composite infiltration layer; 203-AlN-ZrO2 intermediate coating; 204-surface insulating layer. DETAILED DESCRIPTION

[0044] As used herein:

[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus. The conjunction "consisting of" excludes any unspecified element, step, or component.

[0046] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0047] In these examples, parts and percentages are by mass unless otherwise indicated.

[0048] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0049] The present application provides an insulating screwdriver, comprising a screwdriver rod and an insulating handle, wherein the screwdriver rod comprises a screwdriver rod body and a Zr-Al-N composite diffusion layer, an AlN-ZrO2 intermediate coating and a surface insulating layer which are sequentially stacked from bottom to top on the surface of the screwdriver rod body.

[0050] In a preferred embodiment of the present application, the surface insulating layer includes at least one of a nylon 66 film layer, a polytetrafluoroethylene film layer and a rubber layer, and more preferably a nylon 66 film layer.

[0051] In a preferred embodiment of the present application, the material of the screwdriver rod body includes any one of chrome steel, chrome vanadium steel, chrome molybdenum steel, and chrome molybdenum vanadium steel, for example, it can be Cr12 or Cr12MoV.

[0052] In a preferred embodiment of the present application, the thickness of the Zr-Al-N composite diffusion layer is 10μm-20μm, for example, it can be 10μm, 12μm, 15μm, 18μm, 20μm or any value between 10μm and 20μm; the thickness of the AlN-ZrO2 intermediate coating is 3μm-6μm, for example, it can be 3μm, 4μm, 5μm, 6μm or any value between 3μm and 6μm; the thickness of the surface insulating layer is 4μm-6μm, for example, it can be 4μm, 5μm, 6μm or any value between 4μm and 6μm.

[0053] It should be noted that the structure of the insulated screwdriver of the present application includes but is not limited to a screwdriver rod and an insulating handle. An insulating telescopic head covering the outer surface of the screwdriver rod may be provided at the front end of the screwdriver rod to prevent the screwdriver rod from touching adjacent conductive elements and causing a short circuit during operation. Furthermore, a screw positioning groove may be designed at the front end of the telescopic head to ensure that the screw does not tilt during installation, thereby improving operation efficiency.

[0054] The present application also provides a method for preparing the above-mentioned insulating screwdriver, comprising: after quenching and tempering the screwdriver rod body, successively performing Zr-Al-N co-diffusion treatment, AlN-ZrO2 coating treatment, and evaporation treatment on the surface of the screwdriver rod body to obtain the insulating screwdriver.

[0055] In a preferred embodiment of the present application, the quenching method includes: using one of nitrogen, helium or argon to perform gas quenching treatment.

[0056] It can be understood that quenching refers to the process of rapid cooling using a certain medium after heating to a certain temperature. The cooling rate is related to the size of the workpiece and the medium selected. The larger the workpiece and the more workpieces there are, the longer the cooling time. For some refractory materials, in order to make the structure melt more evenly, they will be kept warm for a period of time when heated to a certain temperature. In common quenching processes, water quenching is mostly used. Although this method has a very fast cooling rate, it is easy to produce residual stress, which in turn causes deformation and cracks in metal materials. Gas quenching is a very gentle quenching method that can form a thin protective layer on the surface of the material to prevent oxidation and corrosion of the metal surface, prevent deformation of the workpiece, and the material is not prone to problems such as hydrogen embrittlement.

[0057] After high-temperature quenching and high-temperature tempering, the hardness of the screwdriver rod body can reach 60-62HRC (or 700Hv-750Hv), and then the screwdriver rod body after quenching and tempering is subjected to a series of coating treatments. The reason why this application adopts high-temperature quenching + high-temperature tempering is that currently low-temperature quenching + low-temperature tempering and high-temperature quenching + high-temperature tempering can make the substrate obtain the same hardness, but if only low-temperature quenching + low-temperature tempering is used, when the coating temperature is higher than the low-temperature tempering temperature, the hardness of the screwdriver rod body obtained will be significantly reduced, even if the hardness of the coating layer is very high, because the hardness of the body is not enough to support the high-hardness film layer, the film layer is easy to fall off under stress; and the hardness of the screwdriver rod body obtained after high-temperature quenching + high-temperature tempering, when the coating temperature is not higher than the low-temperature tempering temperature, the hardness of the screwdriver rod body (60-62HRC) may remain constant.

[0058] In a preferred embodiment of the present application, a Zr-Al-N composite diffusion layer is first prepared on the surface of the screwdriver rod body, the purpose of which is to form intermetallic compounds on the surface of the screwdriver rod body of the screwdriver, further improve the hardness and wear resistance, and reduce the conductivity of the surface of the screwdriver rod body.

[0059] In a preferred embodiment of the present application, the Zr-Al-N co-diffusion treatment includes: using a Zr-Al composite material as a target material for coating, adopting a dual-cathode DC dual power supply, introducing a nitrogen-containing mixed gas, performing co-diffusion treatment, and forming the Zr-Al-N composite diffusion layer.

[0060] Among them, in the Zr-Al composite material, the mass proportion of Zr is 5%-10%, and the mass proportion of Al is 95%-90%, for example, the mass proportion of Zr is 5%, the mass proportion of Al is 95%, or the mass proportion of Zr is 8%, the mass proportion of Al is 92%, or the mass proportion of Zr is 10%, and the mass proportion of Al is 90%.

[0061] When using dual cathode DC dual power supplies for co-penetration treatment, the cathode of one cathode power supply is connected to the Zr-Al composite material as a source, and the working voltage is 700V-800V; the cathode of the other cathode power supply is connected to the screwdriver rod body workpiece as a cathode, and the working voltage is 450V-550V; the anode is connected to the vacuum furnace wall and grounded. At the same time, the temperature is raised to 520℃-550℃, N2 and H2 are injected at a volume ratio of 1:3, and then Ar gas is injected, the vacuum degree in the vacuum furnace is adjusted to 1Pa-10Pa, and the temperature is kept for 3h-4h, and a Zr-Al-N composite penetration layer with a thickness of 10μm-20μm and a hardness of more than 1200Hv is formed on the surface of the screwdriver rod body material, which significantly improves the wear resistance and reduces the conductivity of the screwdriver rod body surface.

[0062] In a preferred embodiment of the present application, after the Zr-Al-N composite diffusion layer is formed, AlN-ZrO2 coating treatment is performed, which specifically includes: using AlN+ZrO2 as the target material, adopting a medium frequency constant voltage coating power supply, the positive pole of the power supply is connected to the workpiece to be coated, and the negative pole is connected to the target material, the voltage is 350V-400V, the frequency is 6KHz-14KHz, the temperature is increased to 200℃-300℃, Ar gas is injected, and then the vacuum degree is adjusted to 1Pa-10Pa, and the heat is kept for 1h-2h to form a layer of AlN-ZrO2 intermediate coating with a thickness of 3μm-6μm.

[0063] Furthermore, in the AlN+ZrO2 target material, the mass proportion of ZrO2 is 5%-10%, and the weight proportion of AlN is 95%-90%, for example, the mass proportion of ZrO2 is 5% and the mass proportion of AlN is 95%, or the mass proportion of ZrO2 is 7% and the mass proportion of AlN is 93%, or the mass proportion of ZrO2 is 10% and the mass proportion of AlN is 90%.

[0064] After forming the AlN-ZrO2 intermediate coating, a surface insulating layer needs to be formed by evaporation, the purpose of which is to further improve the insulation level of the screwdriver rod. Nylon 66 is preferred for evaporation because nylon 66 is an engineering plastic with good strength and a certain degree of ductility, which can wrap the AlN+ZrO2 intermediate film layer, making the intermediate layer less likely to wear or fall off.

[0065] In a preferred embodiment of the present application, the evaporation treatment specifically includes: using nylon 66 as the evaporation material, placing the workpiece to be evaporated into a crucible, injecting Ar gas, adjusting the vacuum degree to 0.5Pa-0.7Pa, raising the temperature to 200℃-300℃, and keeping warm for 1h-2h to form a nylon-66 film layer with a thickness of 4μm-6μm on the surface of the material.

[0066] After high-temperature quenching + high-temperature tempering, Zr-Al-N co-diffusion treatment, AlN+ZrO2 coating treatment and evaporation treatment, the screwdriver rod can achieve the purpose of both pressure resistance and insulation. Within the voltage range of 300V-1500V, the screwdriver can maintain insulation; the screwdriver has high hardness, good wear resistance, good bonding between each film layer, no delamination, and long service life. Among them, the Zr-Al-N composite diffusion layer and the AlN-ZrO2 intermediate film layer both contain Al and Zr elements, which have an affinity and improve the bonding between the composite diffusion layer and the intermediate film layer; the nylon-66 film layer has a certain ductility and can wrap the intermediate film layer, making the AlN-ZrO2 film layer less prone to wear or fall off.

[0067] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0068] Example 1

[0069] This embodiment provides a Figure 1The screwdriver comprises an insulating handle 1 and a screwdriver rod 2. The screwdriver rod 2 comprises a screwdriver rod body 201 and a Zr-Al-N composite infiltration layer 202, an AlN-ZrO2 intermediate coating 203 and a surface insulating layer 204 which are sequentially stacked on the surface of the screwdriver rod body 201. Figure 2 shown.

[0070] The screwdriver rod body 201 of this embodiment is made of Cr12MoV, the surface insulating layer is a nylon-66 film layer, the Zr-Al-N composite infiltration layer 202 is 10 μm thick, the AlN-ZrO2 intermediate coating 203 is 5 μm thick, and the surface insulating layer 204 is 5 μm thick.

[0071] The method for preparing the screwdriver rod in the screwdriver comprises:

[0072] (1) High temperature quenching + high temperature tempering: The screwdriver rod body is quenched at 1100°C using argon gas quenching; then tempered at 550°C.

[0073] (2) Zr-Al-N composite co-penetration: A Zr-Al composite material is used as the target material, in which the mass proportion of Zr is 5% and the mass proportion of Al is 95%. A dual-cathode DC dual power supply is used, the cathode of one cathode power supply is connected to the Zr-Al target material, the working voltage is 700V, and the cathode of the other cathode power supply is connected to the workpiece with a working voltage of 450V. The anode is the vacuum furnace wall and is grounded. The temperature in the vacuum furnace is 520℃. N2 and H2 are injected at a volume ratio of 1:3, and then Ar gas is injected. The vacuum degree in the furnace is adjusted to 5Pa and kept warm for 3 hours to form a Zr-Al-N composite infiltration layer with a thickness of 10μm and a hardness of more than 1200Hv.

[0074] (3) AlN-ZrO2 coating treatment: AlN+ZrO2 is used as the target material, in which the mass proportion of AlN is 5% and the mass proportion of ZrO2 is 95%; a medium-frequency constant voltage coating power supply is used, with a voltage of 400V and a frequency of 10KHz. The positive pole of the power supply is connected to the workpiece and the negative pole is connected to the target material; the temperature is 250°C; Ar gas is injected, the vacuum degree in the furnace is adjusted to 5Pa, and the insulation time is 1.5 hours to form a 5μm thick AlN-ZrO2 intermediate coating.

[0075] (4) Nylon-66 evaporation treatment: Nylon-66 is used as the evaporation material. The workpiece is placed in a crucible, and Ar gas is injected. The vacuum degree in the furnace is adjusted to 0.5 Pa, the temperature is 200°C, and the insulation time is 1.5 hours to form a nylon-66 insulating film layer with a thickness of 5 μm.

[0076] Example 2

[0077] The structure and preparation method of the screwdriver of this embodiment are the same as those of Embodiment 1, except that: the mass proportion of Zr in the Zr-Al composite material in step (2) is 10%; and the content of Al is 90%.

[0078] Example 3

[0079] The structure and preparation method of the screwdriver of this embodiment are the same as those of Embodiment 1, except that in the AlN+ZrO2 target material in step (3), the mass proportion of AlN is 90% and the mass proportion of ZrO2 is 10%.

[0080] Comparative Example 1

[0081] The screwdriver of this comparative example is the same as that of Example 1, except that there is only a ferroferric oxide film (obtained by blackening the surface) on the surface of the screwdriver rod body 201 .

[0082] Comparative Example 2

[0083] The screwdriver of this comparative example is the same as that of Example 1, except that there is only a 4 μm Al 2 O 3 film layer (obtained by PVD coating of Al 2 O 3 ) on the surface of the screwdriver shaft body 201 .

[0084] Comparative Example 3

[0085] The screwdriver of this comparative example is the same as that of Example 1, except that: a 4 μm AlN film layer and a 5 μm polytetrafluoroethylene surface film layer (obtained by PVD coating AlN + spraying polytetrafluoroethylene) are provided on the surface of the screwdriver shaft body 201 .

[0086] The above embodiments and comparative examples were tested for insulation, withstand voltage and bonding strength, and the test results are shown in Table 1. The specific test methods are as follows:

[0087] Insulation test: Use a multimeter to test the resistance of the screw starter rod 3 at a set voltage. One pole of the multimeter is connected to the front end of the starter rod 3, and the other pole is connected to a position 0.5cm-4cm away from the front end of the starter rod and moved randomly. The resistance value obtained by the test is not less than 3GΩ to be qualified.

[0088] Wear resistance and bonding strength test: Use the company's dedicated cycle torque tester, install the screwdriver on the test rod, tighten and loosen the given screw 10,000 times under the set torque, remove the screwdriver, and test the insulation performance of the rod 3. The test method is the same as above. If the insulation test is qualified, the wear resistance test is deemed qualified.

[0089] Table 1 Test results of various embodiments and comparative examples

[0090] Sample No. Insulation properties Wear resistance and bonding strength Comparative Example 1 Resistor 16kΩ (unqualified) The film layer falls off, the resistance is 1.1kΩ (unqualified) Comparative Example 2 Resistance 2.8GΩ (unqualified) The film layer falls off, the resistance is 1.3kΩ (unqualified) Comparative Example 3 Resistance 783GΩ (qualified) The film layer falls off, the resistance is 1.8kΩ (unqualified) Example 1 Resistance 396GΩ (qualified) The film layer does not fall off, the resistance is 8.9GΩ (qualified) Example 2 Resistance 375GΩ (qualified) The film does not fall off, the resistance is 6.4GΩ (qualified) Example 3 Resistance 423GΩ (qualified) The film does not fall off, the resistance is 7.8GΩ (qualified)

[0091] It can be seen from Table 1 that the screwdriver prepared by the preparation method of the embodiment of the present application can maintain insulation when used in the voltage range of 300V-1500V, and the screwdriver has good wear resistance and can be used for a long time.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0093] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, any of the above-mentioned claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. An insulated screwdriver, characterized in that: The invention comprises a screwdriver rod and an insulating handle. The screwdriver rod comprises a screwdriver rod body and a Zr-Al-N composite infiltration layer, an AlN-ZrO2 intermediate coating layer and a surface insulating layer which are sequentially stacked on the surface of the screwdriver rod body.

2. The insulated screwdriver according to claim 1, characterized in that: The surface insulating layer includes at least one of a nylon 66 film layer, a polytetrafluoroethylene film layer and a rubber layer.

3. The insulated screwdriver according to claim 1, characterized in that: The thickness of the Zr-Al-N composite diffusion layer is 10 μm-20 μm; The thickness of the AlN-ZrO2 intermediate coating is 3 μm-6 μm; The thickness of the surface insulating layer is 4 μm-6 μm.

4. The insulated screwdriver according to any one of claims 1 to 3, characterized in that: The material of the screwdriver rod body includes any one of chrome steel, chrome vanadium steel, chrome molybdenum steel, and chrome molybdenum vanadium steel.

5. A method for preparing an insulating screwdriver according to any one of claims 1 to 4, characterized in that: include: After the screwdriver rod body is subjected to quenching and tempering treatments, Zr-Al-N co-penetration treatment, AlN-ZrO2 coating treatment, and vapor deposition treatment are sequentially performed to obtain the insulating screwdriver.

6. The preparation method according to claim 5, characterized in that: At least one of the following conditions is met: a. The quenching method includes: using nitrogen, helium or argon gas quenching treatment; b. The Zr-Al-N co-penetration treatment comprises: using a Zr-Al composite material as a target material for coating, using a dual cathode DC dual power supply, passing a nitrogen-containing mixed gas, and performing a co-penetration treatment to form the Zr-Al-N composite permeation layer; c. The AlN-ZrO2 coating process comprises: using AlN+ZrO2 as a target material, using a medium frequency constant voltage coating power supply, performing a coating process to form the AlN-ZrO2 intermediate coating layer; d. The evaporation treatment includes: using nylon-66 as the evaporation material, and evaporating to form the surface insulating layer under vacuum conditions.

7. The preparation method according to claim 6, characterized in that: At least one of the following conditions is also met: e. In the Zr-Al composite material, the mass proportion of Zr is 5%-10%, and the mass proportion of Al is 95%-90%; f. The electrode connection method and power supply parameters of the dual cathode DC dual power supply are as follows: the cathode of one cathode power supply is connected to the Zr-Al composite material as a source, and the operating voltage is 700V-800V; the cathode of the other cathode power supply is connected to the workpiece as a cathode, and the operating voltage is 450V-550V; the anode is connected to the vacuum furnace wall and grounded; g. The mixed gas further comprises hydrogen, and the volume ratio of the nitrogen to the hydrogen is 1:(2-3); h. During the co-penetration treatment, the vacuum degree of the vacuum furnace is 1Pa-10Pa, and the temperature is 520℃-550℃; i. The co-osmosis treatment time is 3h-4h.

8. The preparation method according to claim 6, characterized in that: At least one of the following conditions is also met: j. In the AlN+ZrO2 target, the mass proportion of ZrO2 is 5%-10%, and the mass proportion of AlN is 95%-90%; k. The electrode connection method of the medium frequency constant voltage coating power supply is: the positive electrode of the power supply receives the workpiece to be coated, and the negative electrode is connected to the target; l. The voltage of the medium frequency constant voltage coating power supply is 350V-400V, and the frequency is 6KHz-14KHz; m. The coating process is carried out under vacuum conditions of 1Pa-10Pa; n. The coating treatment temperature is 200°C-300°C and the time is 1h-2h.

9. The preparation method according to claim 5, characterized in that: At least one of the following conditions is also met: o. After the tempering treatment, the hardness of the screwdriver rod body is 700Hv-750Hv; p. After the Zr-Al-N co-diffusion treatment, the hardness of the Zr-Al-N composite diffusion layer is 1200Hv-1250Hv.

10. The preparation method according to any one of claims 5 to 9, characterized in that: The vacuum conditions of the evaporation treatment are 0.5Pa-0.7Pa, the temperature is 200°C-300°C, and the time is 1h-2h.

Citation Information

Patent Citations

  • High oxidation resistance nanocrystalline-amorphous structured superhard composite film cutting tool and deposition method therefor

    CN1654702A

  • Process for preparing ZrN / Al2 (O1-xNx)3 hard nano multi-layer coating

    CN1793415A